Evolution of tactical approaches to eliminating limb length discrepancy - Konstantin I. Novikov; Elina S. Komarova; Sergei V. Kolesnikov; Oleg V. Klimov; Konstantin S. Sergeev (Гений oртопедии, 2024)
Introduction Limb length discrepancy (LLD) can be debilitating and may cause other medical and social problems. LLD is a serious physical condition and have a significant impact on the patient's quality of life changing the gait, forming pathological adaptive mechanisms and causing long-term musculoskeletal disturbances in children. The objective was to analyze the evolution of tactical approaches to the rehabilitation of patients with lower limb length inequality. Material and methods The original literature search was conducted on key resources including Scientific Electronic Library (www.elibrary.ru) and the National Library of Medicine (www.pubmed.org). Literature searches included both Russian and English studies. The search strategy was comprised of keywords: lower limbs, limb length inequality, approaches and means of limb length correction, osteosynthesis. Clinical guidelines, clinical recommendations, systematic reviews, randomized controlled trials and multicenter cohort studies were selected for analysis. Results and discussion Normal individuals can often experience a difference in the length of the lower limbs from several mm to 1.5 cm and have no effect on the gait, condition of adjacent joints and joints of the opposite limb. Some authors report inequality of 5 mm leading to orthopaedic pathology. A variety of conservative and surgical treatments are offered for limb length equalization. Elimination of LLD is a common and unresolved medical problem. Conservative treatment of LLD can be considered as one of the stages of rehabilitation. Some patients can benefit from conservative treatments. Alternatively, surgical equalization is a treatment option for patients with LLD. Conclusion Surgical methods offered earlier to address LLD had disadvantages, which ultimately minimized their use, and orthopaedic surgeons abandoned some of them due to the high risk of severe complications. The device and the technique developed by Dr. Ilizarov in the 50s of the last century was an epoch-making event in the elimination of LLD and are constantly being improved.